Associação da disfunção temporomandibular com o polimorfismo 102T-C do gene do receptor da serotonina HTR2A - Freitas, Luciana Secches de (2011)
Introduction: Serotonin is an important neurotransmitter in the central nervous system. It has been suggested that serotoninergic dysfunction mediates the pathophysiology of temporomandibular dysfunction (TMD). Polymorphisms in HTR2A gene can alter the number of receptors in the serotoninergic system, causing nociceptive pain and hyperalgesia in the TMD. Objective: The aim of this study is to determine the prevalence of the 102T-C polymorphism of HTR2A in patients with and without TMD. Casuistic and Method: This cross-sectional study examined 100 patients as index cases and 100 persons as controls, of both genders. DNA was extracted from peripheral blood leukocytes, and the site that encompassed the polymorphism was amplified by PCR-RFLP. Results: There were significantly more females among index cases compared with the control group (p<0.05). The CC genotype of the 102T-C polymorphism was more frequent in patients with TMD versus controls (OR: 2.25; CI 95%: 1.13-4.46; p<0.05). Conclusions: The 102T-C polymorphism of HTR2A gene is linked to TMD in the studied population.